Accidental injection of 2% chlorhexidine gluconate instead of an anesthetic agent: A case report - Hiremath, Hemalatha (J Conserv Dent, 2016)
We report a case where 2% chlorhexidine (CHX) gluconate was mistaken for an anesthetic solution and infiltrated into the buccal vestibule during routine root canal treatment. Accidentally, 2% CHX gluconate solution was injected in the right upper buccal vestibule (16) of a 23-year-old male during routine root canal treatment. The patient experienced pain and a burning sensation over the injected area shortly after injection. Swelling with mild extraoral redness over the right cheek area was observed clinically. The patient was immediately administered dexamethasone intramuscularly, and was prescribed antibiotics, analgesics, and antihistamines. The patient complained of a loss of sensation over the right cheek by the 15(th) day. The swelling reduced gradually over a period of 15 days. Reversal of sensation was attained after 35 days.